2003
DOI: 10.1200/jco.2003.02.098
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Gemcitabine Versus the Matrix Metalloproteinase Inhibitor BAY 12-9566 in Patients With Advanced or Metastatic Adenocarcinoma of the Pancreas: A Phase III Trial of the National Cancer Institute of Canada Clinical Trials Group

Abstract: Gemcitabine is significantly superior to BAY 12-9566 in advanced pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
168
2
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 357 publications
(178 citation statements)
references
References 17 publications
4
168
2
4
Order By: Relevance
“…However, as summarized in Table 4, with the exception of erlotinib, the completed phase III trials have not confirmed an important clinical benefit [45][46][47][48][49][50][51].…”
Section: Gemcitabine Plus Erlotinib: Statistical Significance Versus mentioning
confidence: 99%
“…However, as summarized in Table 4, with the exception of erlotinib, the completed phase III trials have not confirmed an important clinical benefit [45][46][47][48][49][50][51].…”
Section: Gemcitabine Plus Erlotinib: Statistical Significance Versus mentioning
confidence: 99%
“…Chemotherapy as a sole modality improves survival in patients with locally advanced or metastatic disease (Palmer et al, 1994;Glimelius et al, 1996); however, even with the current regimens, median overall survival has ranged from 3.3 to 11.5 months in phase II trials and has generally been not more than 7 months in phase III trials (Burris et al, 1997;Berlin et al, 2002;Colucci et al, 2002;Maisey et al, 2002;Moore et al, 2003;Petty et al, 2003;Rocha Lima et al, 2004;Lopes and Rocha Lima, 2005;Louvet et al, 2005;Oettle et al, 2005). There is little published information on the effectiveness of chemotherapy alone in preventing local failure, but an apparent improvement in survival has been reported in two recent large phase III studies, which had a significant subset of patients with locally advanced disease Poplin et al, 2006a).…”
mentioning
confidence: 99%
“…Newer cytotoxic agents such as premetrexed , exatecan (Cheverton et al, 2004;O' Reilly et al, 2004), oxaliplatin (Louvet et al, 2005), irinotecan (Rocha Lima et al, 2004) and novel agents targeting matrix metalloproteinase (Bramhall et al, 2001(Bramhall et al, , 2002Moore et al, 2003), and farnesyltransferase (Van Cutsem et al, 2004) had all entered phase III testing either alone or in combination with gemcitabine -the current standard of care. Yet despite these efforts, none of these drugs have shown an OS advantage over gemcitabine monotherapy.…”
Section: Discussionmentioning
confidence: 99%